Exploiting phenotypic and genotypic diversity against colletotrichum truncatum in chilli hybrids developed using resistant breeding lines - Herath, H.M.S.N.; Rafii, M. Y.; Ismail, Siti Izera; Jaafar, Juju Nakasha; Ramlee, Shairul Izan (Cambridge University Press, 2024)
In an effort to control anthracnose disease, one of the major problems that has been faced by farmers, 14 chilli hybrids and their parents were screened phenotypically using the fruit inoculation method under laboratory conditions. Genotypic screening of 14 chilli hybrids and their parents was done by the identified polymorphic markers, HpmsE 051 and HpmsE 082. Based on the phenotypic and genotypic data, chilli hybrids, H1, H2, H3, H4, H6, H7, H8, H9, H11 and H12 were identified as resistant chilli hybrids against anthracnose disease caused by the C. truncatum. Molecular markers, HpmsE 051 and HpmsE 082 could be utilized as polymorphic markers to isolate resistant genotypes against C. truncatum.